Organizacja procesu badania efektywności przedsięwzięć informatycznych - Dudycz, Helena; Dyczkowski, Mirosław (The organization of evaluation process of it projects, 2006)
This paper describes and characterizes the main factors which determine the procedure of evaluation of IT projects : time of evaluation execution , target, subject and object. Based on this description the idea of organization of evaluation process is proposed. This idea can be used to developing the methodology of economical appraisal of information technology investment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 234-244